Investigación-acción : retroalimentación invertida para el desarrollo de competencias de escritura académica en inglés (2017)
"With the advancement of the digital age and the continuous development of information and communication technologies, new demands and challenges arise, including the integration of technological innovations to education. Currently, flipped learning is one of the trending innovations, and it has shown it is effective to improve educational processes. This research about the use of flipped learning in academic writing is located in this context. Its objective was to evaluate the effect of flipping the feedback given to academic paragraphs in the process of developing writing competence in English as an international language. Through an action research, I conducted an intervention which included two feedback phases, written and flipped, to the products that were the result of the writing process of an academic paragraph: planning, drafting, revising, and editing." -- Tomado del Formato de Documento de Grado.